Cocaine Induced Vasculitis: Have We Found a Culprit? - Alfredo Sánchez-Cruz; Sylmarie Marrero; José Betancourt; Myrna Andino; Adolfo Lopez; Jose Gutierrez-Nuñez (Case Reports in Rheumatology)
Cocaine abuse is relatively common in our society. To enhance profitability and acceptability of the product, it is not uncommon for illicit drugs to undergo several processes. The Drug Enforcement Agency (DEA) has reported that seventy percent (70%) of cocaine seized at USA borders has been adulterated with levamisole, previously used as chemotherapeutic and immunomodulator for several conditions. Among the side effects of levamisole-adulterated cocaine, necrotizing vasculitis is the more dramatic. We report three cases of necrotizing vasculitis associated with antineutrophils cytoplasmic antibodies (ANCAs) positivity, linked to the use of cocaine. To our knowledge, these are the first cases of cocaine induced vasculitis reported in the Caribbean.